Evolution of wildfires under a greenhouse climate: A case study from the early Middle Jurassic in the Ordos Basin, China - Jianbo Hu; Si Chen; Mian Zhang; Chunhui Mu; Weixing Long; Tianyou Wang; Yingchun He; Xiaoming Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Enhancement of calcium oxide on hydrogen production and degradation of polylactic acid microplastics in anaerobic fermentation - Xiaoxuan Zhu; Ruirui Shang; Xi Yang; Chuanzheng Song; Hui Mu; Chunhui Zhao; Huanhuan Guo; Yongfang Zhang (Journal of Environmental Management, 2026)

Fe3O4 nanoparticles and cytochrome c synergistically facilitate lactate chain elongation to caproate - Yichao Wang; Chunhui Zhao; Fangyuan Feng; Yaomin Xi; Wenhan Chen; Xiaoyu Zhu; Xiang Li; Chuanshun Zhi; Hui Mu (Journal of Environmental Chemical Engineering, 2026)

Mechanistic insights into sulfidated nanoscale zero-valent iron enhanced methanogenesis: Electron redistribution and direct interspecies electron transfer-driven metabolic reconfiguration - Fangyuan Feng; Chunhui Zhao; Yinguang Chen; Yongfang Zhang; Xiaonong Hu; Hui Mu; Wen Zhang (Bioresource Technology, 2026)

Development of a magnetite-oyster shell composite to improve methanogenesis in carbohydrate-rich wastewater treatment - Fangyuan Feng; Yichao Wang; Jingyang Luo; Chunhui Zhao; Yongfang Zhang; Chuanshun Zhi; Hui Mu (Journal of Environmental Chemical Engineering, 2025)

Oyster shell immobilized nano zero-valent iron for enhancing methane production from carbohydrate-rich food waste: Characterization, performance, and mechanism - Xiaofan Ding; Wei Jiang; Fangyuan Feng; Bochang Feng; Yanfei Li; Yongfang Zhang; Chuanshun Zhi; Chunhui Zhao; Jingyang Luo; Hui Mu (Journal of Environmental Chemical Engineering, 2025)

Determination of nitrofuran metabolites in fish samples by boronate affinity extraction coupled to HPLC-MS/MS using cis diol-modified mesoporous polymer (GMA-EGDMA) microspheres as adsorbents - Wendi Huo; Jincheng Li; Yupeng Wen; Xinyuan Zhang; Huan Liu; Yingchun Mu; Chunhui Zhao; Chaoying Zhang; Rongyue Zhang (Journal of Hazardous Materials, 2025)

Ecological Responses of Microbially Activated Water Flooding in Ultra-Low-Permeability Reservoirs: A Case Study of the B9 Reservoir in the Triassic Yanchang Formation - Lei Li; Chunhui Zhang; Peidong Su; Hongmei Mu (Journal of Marine Science and Engineering, 2025)
The impact of anthropogenic disturbances during reservoir development on the ecological system—encompassing both environmental and microbial components—has long been overlooked. This study pioneers the investigation into the effects of microbially activated water flooding on both reservoir environments and indigenous microbial communities. We conducted a comprehensive analysis of the B9 Reservoir’s parameters before and after field testing, including the pH, redox potential, conductivity, chemical oxygen demand, biochemical oxygen demand, aqueous-phase cell concentration, aqueous-phase deoxyribonucleic acid (DNA) concentration, oil-phase DNA concentration, and microbial population data. The results demonstrate that environmental parameters exhibit high sensitivity to microbially activated water flooding and effectively explain microbial blooms, while microbial blooms reciprocally alter the environmental conditions, forming a mutually influencing dynamic interplay. The 183-day microbially activated water flooding, while causing detectable impacts on the reservoir environment and microorganisms, did not pose a threat to its ecological stability and contributed to enhanced oil production. In contrast, the 60-month pilot test concluded 27 months earlier exhibited potential destabilization risks to the reservoir ecology. By simultaneously monitoring reservoir environments and microbial dynamics, this research not only addresses potential ecological risks associated with human-driven reservoir development but also provides actionable insights to optimize reservoir management strategies.

A critical review on the activation of peroxymonosulfate by MOFs for antibiotics degradation: Affecting factor, performance and mechanism - Yiyun Li; Chunhui Zhang; Guifeng Zhao; Zhao Zhang; Peidong Su; Yanxin Li; Yonglin Mu; Weilong Zhou (Journal of Environmental Chemical Engineering, 2024)

A critical review on antibiotics removal by persulfate-based oxidation: Activation methods, catalysts, oxidative species, and degradation routes - Yanxin Li; Chunhui Zhang; Guifeng Zhao; Peidong Su; Jianbing Wang; Yiyun Li; Weilong Zhou; Yonglin Mu; Junke Zhang; Wenzong Liu (Process Safety and Environmental Protection, 2024)

Significant enhancement of biomethane recovery in up-flow anaerobic sludge blanket reactor treating starch wastewater through oyster shells conditioning - Hui Mu; Qingyu Sun; Meng Zhong; Chunhui Zhao; Yongfang Zhang; Liguo Wang (Journal of Cleaner Production, 2023)

Effects of different types of granular activated carbon on methanogenesis of carbohydrate-rich food waste: Performance, microbial communities and optimization - Hui Mu; Xiaofan Ding; Xiaoyu Zhu; Liguo Wang; Yongfang Zhang; Chunhui Zhao (Science of The Total Environment, 2023)